Pengaruh Ukuran Perusahaan, Net Profit Margin Dan Debt To Equity Ratio Terhadap Pertumbuhan Laba PT Bukit Asam Tbk Periode 2015-2024 - Mazida Hapsari; Lina Nofiana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study aims to determine and analyze the extent of the influence of Firm Size, Net Profit Margin, and Debt to Equity Ratio on Profit Growth at PT Bukit Asam Tbk for the 2015–2024 period, both partially and simultaneously. The research method used is quantitative, employing financial statement data. The analytical methods applied include descriptive tests, classical assumption tests, linear regression analysis, hypothesis testing, and coefficient determination. The combination of these factors provides a strong overall impact on Profit Growth. The coefficient of determination test shows a value of 0.531 or 53.1%, indicating that Firm Size, Net Profit Margin, and Debt to Equity Ratio collectively influence Profit Growth by 53.1%, while the remaining 46.9% is influenced by other variables not included in this study. The results show that Firm Size has no significant partial effect (t-count -0.113 > t-table 2.447 with a significance value of (0.914 > 0.05). The test results for Net Profit Margin indicate a significant positive effect (t-count 2.974 < t-table 2.447) with a significance value of (0.025 < 0.05). The test results for Debt to Equity Ratio show a significant negative effect (t-count -3.331 < t-table 2.447) with a significance value of (0.016 < 0.05). Simultaneously, Firm Size, Net Profit Margin, and Debt to Equity Ratio have a significant effect on Profit Growth (f-count 9.153 > f-table 4.757) with a significance value of (0.012 < 0.05).